POLA KLUSTER, FORMASI KETERKAITAN, DAN ORIENTASI PASAR PADA SENTRA INDUSTRI TEMPE (Fokus Ekonomi, 2011)
This study analyzes cluster pattern, linkage formation, and variables determining market orientation of small and cottage industries in Pliken, Kembaran, Banyumas. The Markusen cluster tipology is used to identify cluster pattern based on the characteristic of small and cottage industries cluster. The result shows that Pliken cluster is Marshallian pattern. It has a weak backward linkage in the production, but it has strong forward linkages in the production, and trading that give more value added. Using logistic regression model this research analyzes market orientation of these industries either in local markets or outside them with some predictors. The regression result shows that market orientations are significantly and positively affected by education of workers and skilled entrepreneurs. These variables give probability for entrepreneurs to make market orientation of their product to outside of  local markets.